Compliance with Oral Antihyperglycemic Medication and Fasting Blood Sugar Levels in Type 2 Diabetes Mellitus Patients - Siswidiasari, Arifani; Sari, Yanti Purnama (Jurnal Ilmiah STIKES Yarsi Mataram, 2026)
Diabetes mellitus is an endocrine disease characterized by hyperglycemia, characterized by elevated blood glucose levels. The cause of elevated blood glucose levels is due to ineffective insulin secretion, insulin action, or both. The purpose of this study was to determine the relationship between adherence to oral antihyperglycemic medication and fasting blood sugar levels in patients with type 2 diabetes mellitus. This study employed a non-experimental, descriptive cross-sectional design. This study was conducted at the Balerejo Community Health Center in Madiun in February 2024 with a total sample of 63 patients. The sampling technique used was the consecutive sampling method. The data analysis used in this study was the Spearman Rank test. The results of the most gender characteristics were female 37 people (58.7%), age 46-55 years 35 people (55.6%), high school education 29 people (46.0%), farmer occupation 11 people (17.5%), normal BMI (18.5-22.9 kg / m2) 25 people (39.7%), metformin monotherapy treatment 11 people (17.5%), metformin + glibenclamide combination 24 people (38.1%). Compliance with taking medication was categorized as compliant in 39 people (61.9%), and non-compliant in 24 people (38.1%). Fasting blood sugar (FBS) targets were achieved by as many as 36 people (57.1%), and not achieved by 27 people (42.9%). The results of the analysis showed significant relationship between compliance with oral antihyperglycemic drugs and fasting blood sugar levels in patients with type 2 diabetes mellitus, with a p-value of 0.000 and a correlation coefficient of 0.510. Conclusion: There is a significant relationship exists between compliance with oral antihyperglycemic drugs and fasting blood sugar levels in type 2 diabetes mellitus patients.